JURNALISME WARGA RADIO KOMUNITAS INDUK BALERANTE DALAM KOMUNIKASI BENCANA ERUPSI MERAPI TAHUN 2010 - Gilang Akbar Noviansyah (2013)
Information to guide all parties to take a rescue scenario and give help, but commercialism is so strong factor in the world of broadcasting Indonesia also made a lot of media as if dancing on the suffering of disaster victims. In the 2010 eruption of events shows that the media is so dramatize the disaster, for example, is a reporter for TV One reports on the eruption of Merapi in 2010. At that time the reporter reports that "heat clouds has been felt in the Kaliurang Km 6.2" where the reporter